Prospective Comprehensive Genomic Profiling of Advanced Gastric Carcinoma Cases Reveals Frequent Clinically Relevant Genomic Alterations and New Routes for Targeted Therapies. (16th April 2015) - Ali, Siraj M.; Sanford, Eric M.; Klempner, Samuel J.; Rubinson, Douglas A.; Wang, Kai; Palma, Norma A.; Chmielecki, Juliann; Yelensky, Roman; Palmer, Gary A.; Morosini, Deborah; Lipson, Doron; Catenacci, Daniel V.; et al.
Abstract : Background: Gastric cancer (GC) is a major global cancer burden and the second most common cause of global cancer‐related deaths. The addition of anti‐ERBB2 (HER2) targeted therapy to chemotherapy improves survival for ERBB2 ‐amplified advanced GC patients; however, the majority of GC patients do not harbor this alteration and thus cannot benefit from targeted therapy under current practice paradigms. Materials and Methods: Prospective comprehensive genomic profiling of 116 predominantly locally advanced or metastatic (90.0%) gastric cancer cases was performed to identify genomic alterations (GAs) associated with a potential response to targeted therapies approved by the U.S. Food and Drug Administration or targeted therapy‐based clinical trials. Results: Overall, 78% of GC cases harbored one clinically relevant GA or more, with the most frequent alterations being found in TP53 (50%), ARID1A (24%), KRAS (16%), CDH1 (15%), CDKN2A (14%), CCND1 (9.5%), ERBB2 (8.5%), PIK3CA (8.6%), MLL2 (6.9%), FGFR2 (6.0%), and MET (6.0%). Receptor tyrosine kinase genomic alterations were detected in 20.6% of cases, primarily ERBB2, FGFR2, and MET amplification, with ERBB2 alterations evenly split between amplifications and base substitutions. Rare BRAF mutations (2.6%) were also observed. One MET ‐amplified GC patient responded for 5 months to crizotinib, a multitargeted ALK/ROS1/MET inhibitor. Conclusion: Comprehensive genomic profiling of GC identifies clinically relevant GAs that suggest benefit from targeted therapy including MET ‐amplified GC and ERBB2 base substitutions. Abstract : Prospective comprehensive genomic profiling of 116 predominantly locally advanced or metastatic gastric cancer (GC) cases was performed to identify genomic alterations (GAs) associated with a potential response to targeted therapies or targeted therapy‐based clinical trials. Comprehensive genomic profiling of GC identified clinically relevant GAs that suggest benefit from targeted therapy including MET ‐amplified GC and ERBB2 base substitutions. Abstract : 摘要 背景 . 胃癌（GC）在全球范围都是严重的癌症负担，同时也是全球癌症相关死亡的第二大原因。化疗联合抗ERBB2（HER2）靶向治疗改善了 ERBB2 扩增的进展期胃癌患者的生存；但是多数胃癌患者的肿瘤中并没有这一基因变异，因此不能从这一治疗范例的靶向治疗中获益。 材料与方法 . 对116例患者进行前瞻性综合性基因组分析，以鉴别与靶向治疗（美国食品和药物管理局批准的靶向治疗，或以靶向治疗为基础的临床试验）部分缓解相关的基因变异（GA），患者主要为局部进展期或转移性胃癌（90.0%）。 结果 . 总体而言，78%的胃癌病例含有≥ 1个临床相关性GA。最常见的基因变异见于 TP53 （50%）、 ARID1A （24%）、 KRAS （16%）、 CDH1 （15%）、 CDKN2A （14%）、 CCND1 （9.5%）、 ERBB2 （8.5%）、 PIK3CA （8.6%）、 MLL2 （6.9%）、 FGFR2 （6.0%）和 MET （6.0%）。20.6%的病例可检测到受体酪氨酸激酶基因变异，主要为 ERBB2 、 FGFR2 和 MET 扩增，而 ERBB2 变异中扩增和碱基置换各占一半。还观察到少量 BRAF 突变（2.6%）。一例 MET 扩增胃癌患者经克唑替尼（ALK/ROS1/MET多靶点抑制剂）治疗5个月有应答。 结论 . 对胃癌进行综合性基因组分析可鉴别出临床相关性GA，提示可从针对包括 MET 扩增胃癌和 ERBB2 碱基置换在内的靶向治疗中获益。 The Oncologist 2015;20:499–507